Amina Mohammed: “I foresee a world without poverty” - Amina J. Mohammed (Africa Renewal, 2015)
Amina Mohammed is the United Nations secretary-general’s former special adviser on post-2015 development planning. She was heavily involved in planning the Sustainable Development Goals (SDGs), a new development agenda to be implemented over the next 15 years, and in getting UN member states, the private sector and civil society to agree on them. The SDGs were formally adopted by 193 countries on 25 September. In this exclusive interview with Africa Renewal’s Kingsley Ighobor, Ms. Mohammed talks about the evolution of the process, the commitments made, the challenges ahead, and why the goals, if implemented, could transform the world.